Stability, functionality and biosafety of Nicotiana Tabacum expressing anti-CMV antibodies / Ng Cheah Wei - Ng, Cheah Wei (2014)
Mosaic Virus (CMV) is a significant plant pathogen affecting various crops and plants in Malaysia. A single chain variable fragment (scFv) anti-CMV antibody was successfully developed via a scFv library constructed with mRNA from the spleen cells of a CMV coat protein-immunized mouse and transformed by Agrobacterium tumefaciens into tobacco plants (Nicotiana tabacum L. cv. White burley). In this study, the performance of primary transformants and 3 successive generations of Nicotiana tabacum expressing anti-CMV scFv were evaluated. An overall of 20% reduction in seed germination was observed as compared to wild type tobacco. All 4 generations did not exhibit any unusual phenotype other than delayed flowering times. The presence of anti-CMV scFv transgene in all 4 generations was detected by polymerase chain reaction (PCR) and confirmed via southern hybridization. Western Blot analysis showed low levels of detectable expressed anti-CMV scFv transgene in T1 and T2 generations. The binding activities of the expressed scFv were then evaluated using ELISA and Dot Blot Assay. Almost no functional activity of trasngenes and no expressed genes were detected in T3 generation. In a challenge assay, early disease symptoms including leaf mosaic and chlorosis were observed on wild type and sensitive transgenic plants 2 weeks after inoculation with CMV. A computer simulation study was carried out via the AutoDock program to reveal the potential binding interaction of anti-CMV scFv to CMV. In compliance with the Malaysian Biosafety Act, a pilot framework for risk assessment and risk management protocol was developed in this study.